RISK MANAGEMENT OF DUE TO EXPOSURE TO PESTICIDE POISONING FOR TOBACCO FARMERS IN THE JEMBER DISTRICT - Eri Witcahyo; Isa Ma’rufi (UPT Penerbitan Universitas Jember)
The main problem is the use of pesticides at thistime when farmers use pesticides and not on thebasis of necessity be indicative, but carried out